Seroprevalence and Risk Factors Possibly Associated with Emerging Zoonotic Vaccinia Virus in a Farming Community, Colombia. (2023)
In 2014, vaccinia virus (VACV) infections were identified among farmworkers in Caquetá Department, Colombia; additional cases were identified in Cundinamarca Department in 2015. VACV, an orthopoxvirus (OPXV) used in the smallpox vaccine, has caused sporadic bovine and human outbreaks in countries such as Brazil and India. In response to the emergence of this disease in Colombia, we surveyed and collected blood from 134 farmworkers and household members from 56 farms in Cundinamarca Department. We tested serum samples for OPXV antibodies and correlated risk factors with seropositivity by using multivariate analyses. Fifty-two percent of farmworkers had OPXV antibodies; this percentage decreased to 31% when we excluded persons who would have been eligible for smallpox vaccination. The major risk factors for seropositivity were municipality, age, smallpox vaccination scar, duration of time working on a farm, and animals having vaccinia-like lesions. This investigation provides evidence for possible emergence of VACV as a zoonosis in South America.